KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DITINJAU DARI GAYA BELAJAR - Hasrianah Abdullah; Sri Satriani; Ernawati Ernawati (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The aim of the study was to describe students' mathematical problem solving abilities in terms of learning styles. This research is qualitative with a qualitative descriptive approach. This research was conducted at SMA Negeri 8 Takalar. The subjects in this study were 3 students from class XI MIPA 1, 1 visual subject, 1 auditory subject, and 1 kinesthetic subject. The instruments used were a learning style questionnaire, a math problem solving test, and an interview guide. Data is obtained by reducing data, presenting data, and drawing conclusions. Checking the validity of the data using the triangulation method. Problem solving is described based on four indicators according to Polya, namely understanding the problem, planning a solution, solving the problem, and looking back. The results of this study indicate that: (1) visual subjects can understand problems, can plan, are less able to solve problems, and look back but are not thorough. (2) auditory subjects can understand the problem, can do planning, less able to solve problems, and do not look back. (3) kinesthetic subjects can understand problems by using fingers as pointers when reading and understanding questions, can plan, can solve problems, and look back.